Assessing Factors Influencing Students’ Choice of Malaysian Public University : A Rasch Model Analysis - Khairani, Ahmad Zamri; Abd. Razak, Nordin (Scientific & Academic Publishing (SAP), 2013)
The purpose of this study is to calibrate factors that influence students in their choice of public university. The factors are university’s image, course offered, facility provided and university’s environment. The participants for this study are 1584 prospective students from pre-university institutions. The study employed a 32-items self-developed questionnaire measuring the mentioned factors. The Rasch Model analyses were used because it provides the researcher with richer interpretations of the data collected. Results showed that the participants endorsed university’s image as the most influential factors followed by university’s environment, facility provided and course offered by the university. Nevertheless, the difference between calibration measures between the factors were small. Thus, the present study suggest that all factors are considered equally important and should be considered as one unitarian factors rather than a few different factors.